MUTU IKAN CAKALANG (Katsuwonus pelamis L) ASAP YANG DIRENDAM DENGAN LARUTAN KULIT BUAH MANGGIS (Gracinia mangostana Linn). - Bentalen, Septian Gedoan; Onibala, Hens; Salindeho, Netty (Media Teknologi Hasil Perikanan, 2017)
The purpose of this study was to determine the quality of smoked skipjack (Katsuwonus pelamis L) smoke pre-treated in a solution of mangosteen peel with a concentration of 3, 4 and 5%, with various soaking time, then stored and observed at 0, 3, 6, and 9 days. The results showed that the highest value of total plate count (TPC) was found in the fish sample storage for 9 days, soaking with a concentration of 3% for 30 minutes. Meanwhile, the lowest TPC value was discovered for the fish samples that did not undergo storage, and immersed in a solution of 5% for 30 minutes. Furthermore, the highest TVB value (Total Volatile bases) was detected in fish samples soaked with 3% solution of the mangosteen for 15 minutes (59.22mg N/100g) while the lowest value obtained on the fish sample marinated with 5% concentration for 15 minutes and did not experience storage (5.04mg N/100g).